Regional and Seasonal Trends in Tropical Ozone From SHADOZ Profiles: Reference for Models and Satellite Products. Issue 22 (18th November 2021) - Thompson, Anne M.; Stauffer, Ryan M.; Wargan, Krzysztof; Witte, Jacquelyn C.; Kollonige, Debra E.; Ziemke, Jerald R.
Abstract: Understanding lowermost stratosphere (LMS) ozone variability is an important topic in the trends and climate assessment communities because of feedbacks among changing temperature, dynamics, and ozone. LMS evaluations are usually based on satellite observations. Free tropospheric (FT) ozone assessments typically rely on profiles from commercial aircraft. Ozonesonde measurements constitute an independent data set encompassing both LMS and FT. We used Southern Hemisphere Additional Ozonesondes (SHADOZ) data (5.8°N–14°S) from 1998 to 2019 in the Goddard Multiple Linear Regression model to analyze monthly mean FT and LMS ozone changes across five well‐distributed tropical sites. Our findings: (a) both FT (5–15 km) and LMS (15–20 km) ozone trends show marked seasonal variability. (b) All stations exhibit FT ozone increases in February‐May (up to 15%/decade) when the frequency of convectively driven waves have changed. (c) After May, monthly ozone changes are both positive and negative, leading to mean trends of +(1–4)%/decade, depending on station. (d) LMS ozone losses reach (4–9)%/decade midyear, correlating with an increase in TH as derived from SHADOZ radiosonde data. (e) When the upper FT and LMS are defined by tropopause‐relative coordinates, the LMS ozone trends all become insignificant. Thus, the 20‐year decline in tropical LMS ozone reported in recent satellite‐based studies likely signifies a perturbed tropopause rather than chemical depletion. The SHADOZ‐derived ozone changes highlight regional and seasonal variability across the tropics and define a new reference for evaluating changes derived from models and satellite products over the 1998–2019 period. Plain Language Summary: Understanding free troposphere (FT) and lowermost stratosphere (LMS) ozone trends is important. If FT ozone increases, it will augment global warming. If LMS ozone has declined in the past 20 years it could mean that something is amiss in atmospheric conditions despite successes of the Montreal Protocol to eliminate ozone‐depleting chemicals from the stratosphere. This study used high‐accuracy, high‐resolution (∼150 m) ozone profiles from balloon‐borne sondes to determine changes over the tropics. The data come from five sites in the Southern Hemisphere Additional Ozonesondes (SHADOZ) archive covering 1998–2019. A summary of results: (a) both FT (5–15 km) and LMS (15–20 km) ozone trends show marked seasonal variability. (b) All stations exhibit strong positive FT ozone trends in the February‐May period but annual means at several stations comparable to the IAGOS record are ≤2%/decade. (c) LMS ozone losses range from (4–9)%/decade midyear and appear to be an artifact of an increasing tropopause height. Therefore, the 20‐year decline in tropical LMS ozone published in satellite‐based studies may signify a perturbed tropopause, that is, a climate signal. Our SHADOZ‐derived ozone trends are available for models, challenging them to reproduce the regional and seasonal variations we find in recent trends. Key Points: Trends (1998–2019) in free troposphere (FT) O3 at five SHADOZ sites are ∼(1–4)%/decade, lower than some satellite or aircraft profile estimates Corresponding lowermost stratospheric (LMS) O3 changes are ∼(−3)%/decade, coinciding with an increase in tropopause height Both FT and LMS O3 trends vary seasonally and regionally, defining new references for evaluating assessment models and satellite products